ANALISIS PERBANDINGAN TINGKAT KESEHATAN DAN KINERJA KEUANGAN PT BPR SUKADANA DENGAN PT BPR SYARIAH DANA MULIA SURAKARTA DENGAN MENGGUNAKAN METODE CAMEL - Djoko Kristianto, Maria Olparika (Universitas Slamet Riyadi, 2015)
This study aims to analyze the comparative level of health and financial performance of aspects CAMEL among BPR with BPRS. CAMEL ratios used consisted of CAR/KPMM, KAP, NPM, ROA, BOPO and Cash Ratio. To distinguish the financial performance of is a statistic analisys is a test used independent sample t-test. The data used is secondary data, financial statement data BPR and BPRS. The results showed that the level of the 2011 - 2013 BPR health of aspects Capital, Asset Quality, earnings, liquidity is healthy, and management aspects are good and while BPRS in the year 2011 - 2013 are ranked 1 aspect Capital, Asset Quality in 2011 ranked second, while in 2012 and 2013 are ranked 1, aspects of earnings in 2011 ranked third, while ranking second in 2012 and in 2013 are ranked 1, aspects of liquidity in 2011 - 2013 are ranked 1, and aspects of management in 2011 not good, while in 2012 and 2013Good. From the test results of independent sample T-Test can be concluded there are significant differences between financial performance PTBPR Sukadana with PT BPRS Dana Mulia. Keywords: level of health, financial performance, methods of CAMEL, BPR.